Enzyme-linked immunosorbent assay for detection of equine infectious anemia virus p26 antigen and antibody. - Shane, B S (J Clin Microbiol, 1984)
A sensitive specific enzyme-linked immunosorbent assay utilizing purified p26 antigen was developed for the detection of antibodies to equine infectious anemia virus in naturally and experimentally infected horses. Generally, antibodies to the virus could be detected by the enzyme-linked immunosorbent assay 3 to 4 days earlier than by the standard agar gel immunodiffusion test, and they could be detected more reliably in horses with weak or equivocal agar gel immunodiffusion test reactions. The enzyme-linked immunosorbent assay was also successfully applied to the detection of p26 antigen in tissue culture fluids.